Voting deliberatively : FDR and the 1936 presidential campaign - Stuckey, Mary E. (Rhetoric and democratic deliberation., 2015)
"An analysis of the constituent elements of Franklin Roosevelt's 1936 presidential election campaign, all of which contributed to his victory then and have proved foundational for the way campaigns and politics more broadly are conducted now"--Provided by publisher